Percepção sobre a prática de cuidados paliativos e terminalidade de vida em um hospital geral - Corradi, Maria Luiza Galoro (2019)
With the progressive aging of the population, it is imperative to understand the need to adapt current medical care, as well as changes in curricular contents in medical schools, to promote teaching and learning of palliative care to patients with incurable diseases, mainly in the final stages of life. This study aimed to evaluate the perception of the attending physicians and medical residents of a general hospital, as well as undergraduate students in internship of the medicine course of the São Camilo University Center on palliative care and end of life; to identify gaps during medical training in issues related to death and dying and Palliative Care, in addition to verifying the difficulties, feelings and attitudes that attending physicians, residents and interns manifest in providing care to patients in the hospital environment. It is a descriptive, transversal study with a predominant qualitative approach. A pilot project was conducted with a total of 8 (eight) attending physicians that were selected at the Medical Clinic Nursing, Intensive Care Unit and Emergency Room units of the Carapicuíba General Hospital in São Paulo; 8 (eight) medical residents of the Medical Clinic Program; and 8 (eight) internist students (9th semester) of the medical course of the São Camilo University Center. After the consent, the participants were applied a structured questionnaire. In a second stage, an interview guided by open questions was performed and recorded with the half of participants in the first stage research by draw and saturation has attained. Using Bardin's content analysis for the interpretation of qualitative results it was concluded from questionnaires that, between the several feelings negatives reported in the confrontation of death (23 respondents), predominated the impotence (n = 16, 69.5%). The vast majority (n = 17, 70.8%) mentioned have participated in discussions about palliative care and end of life occasionally in the graduation, that corresponded with the qualitative results, in which respondents unveil 4 thematic categories: feelings in the face of death and dying; the confrontation death is difficult in everyday practice; they establish the importance of the palliative care and identify graduation as fundamental period for changing this paradigm, through the insertion of these content across the graduation